The International Pharmacy Game: A Comparison of Implementation in Seven Universities World-Wide - Tanja Fens; Denise L. Hope; Sarah Crawshaw; Eline Tommelein; Claudia Dantuma-Wering; Bertha Maria Verdel; Indrė Trečiokienė; Vibhu Solanki; Eugène P. van Puijenbroek; Katja Taxis (MDPI AG, 2021)
The utilization of serious games and simulations in health professional education has increased. The Pharmacy Game is one such concept that intersects gamification and simulation, in which pharmacy student teams competitively manage simulated pharmacies; a concept included in the pharmacy curricula of seven international universities. This study aimed to compare the implementation and conduct of the Pharmacy Game of participant universities and their students' performance in the same educational task. Data were collected via a questionnaire completed by academic staff in April 2020, and the collation of results of the same patient case was conducted at each university (April 2020 to March 2021). The main results reflected differences in the game frequencies and the curricular approach (standalone or integrated course) and in the learning outcomes for the Pharmacy Game. Other differences were identified in the extent to which students of other professions were part of the game such as medical students or pharmacy assistants. Student case outcomes revealed similar strengths across the universities in patient communication and focus on safety, with variations identified as areas for improvement. Collation of the international utilization of the Pharmacy Game identified a broad spectrum of similar learning outcomes, inspiring a model of international core and aspirational learning outcomes. While the Pharmacy Game has been implemented with flexibility regarding the numbers of teams (4-10) and the duration of activity (12-36 days), all universities reported positive experiences and student outcomes, suggesting that the intervention represents a potential tool to deliver capstone learning experiences, promote interprofessional education, reinforce patient safety, and prepare pharmacy graduates for future practice.